The Effect of Technical, Fundamental, and Risk Management Analysis on the Stock Investment Decisions of Investors in Malang Raya - ira farisa surya; Ronny Malavia Mardani; mohamad bastomi (Jurnal Manajemen, 2026)
The purpose of this study is to examine the effect of technical analysis, fundamental analysis, and risk management on stock investment decisions among investors in Malang Raya. This research is grounded in the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), which emphasize the role of analytical capability and perceived behavioral control in shaping rational investment behavior. This study employed a quantitative causal research design involving 126 stock investors selected through purposive sampling based on domicile in Malang Raya and a minimum investment experience of six months. Data were collected using a structured questionnaire measured on a five-point Likert scale and analyzed using Multiple Linear Regression. The results indicate that technical analysis, fundamental analysis, and risk management have a positive and significant effect on stock investment decisions. Among the three variables, risk management emerges as the most dominant factor. The coefficient of determination (R²) of 0.529 indicates that 52.9% of the variance in investment decisions is explained by the proposed model. The findings imply that effective investment decision-making is not only driven by analytical skills related to market and firm evaluation but is strongly influenced by investors’ ability to systematically identify, assess, and mitigate risks. This study contributes theoretically by integrating technical analysis, fundamental analysis, and risk management within the TAM and TPB frameworks, and practically by providing insights for investors and capital market institutions to strengthen investment education programs that emphasize analytical competence and disciplined risk management.